2021
DOI: 10.1186/s40663-021-00318-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of root dominate over aboveground litter on soil microbial biomass in global forest ecosystems

Abstract: Background Inputs of above- and belowground litter into forest soils are changing at an unprecedented rate due to continuing human disturbances and climate change. Microorganisms drive the soil carbon (C) cycle, but the roles of above- and belowground litter in regulating the soil microbial community have not been evaluated at a global scale. Methods Here, we conducted a meta-analysis based on 68 aboveground litter removal and root exclusion studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“… Crow et al (2009) suggested that changes in the quantity of litter and roots can affect soil microbial diversity by changing soil physicochemical properties. The removal of litter and roots hindered C input belowground, decreased soil microbial biomass C and the diversity of the C source available to the microorganisms, and consequently decreased the soil microbial alpha diversity index ( Jing et al, 2021 ). Additionally, the removal of litter and roots reduce understory plant diversity and carbon source input by changing soil nutrients, thus inhibiting soil microbial diversity ( Zhao et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… Crow et al (2009) suggested that changes in the quantity of litter and roots can affect soil microbial diversity by changing soil physicochemical properties. The removal of litter and roots hindered C input belowground, decreased soil microbial biomass C and the diversity of the C source available to the microorganisms, and consequently decreased the soil microbial alpha diversity index ( Jing et al, 2021 ). Additionally, the removal of litter and roots reduce understory plant diversity and carbon source input by changing soil nutrients, thus inhibiting soil microbial diversity ( Zhao et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Soil microbes not only control the decomposition of soil C but also affect the transformation process of soil N (i.e., nitrification and denitrification; Crowther et al, 2015 ; Scarlett et al, 2021 ). It is well known that environmental changes and human activities can alter the quantity of litter and root inputs into the soil in forest ecosystems ( Li et al, 2020 ; Jing et al, 2021 ). These alterations can affect the number and community structure of microorganisms by altering soil nutrient availability and hydrothermal factors ( Liu et al, 2017 ; Santiago et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, plants supply rhizosphere‐associated microorganisms with C (Fan et al, 2022; Jackson et al, 2019) and provide nutrients through aboveground and belowground litter input (Meier & Bowman, 2008). As a consequence, vegetation influences the growth, distribution, and stoichiometry of microorganisms in soils, as demonstrated by the close relationships of microbial biomass with plant root biomass and litter input (Jing et al, 2021; Kara et al, 2008). The relative effects of climate, soil physicochemical properties, and vegetation on soil microbial biomass and stoichiometry are difficult to disentangle and are thus rarely reported at the global scale.…”
Section: Introductionmentioning
confidence: 99%
“…For example, plants supply rhizosphere-associated microorganisms with C (Fan et al, 2022;Jackson et al, 2019) and provide nutrients through aboveground and belowground litter input (Meier & Bowman, 2008). As a consequence, vegetation influences the growth, distribution, and stoichiometry of microorganisms in soils, as demonstrated by the close relationships of microbial biomass with plant root biomass and litter input (Jing et al, 2021;Kara et al, 2008). The relative effects of climate, soil physicochemical properties, and vegetation on soil microbial biomass and stoichiometry are difficult to disentangle and are thus rarely reported at the global scale.…”
Section: Introductionmentioning
confidence: 99%